Flow Control and High-Lift Performance for Flying-Wing Unmanned Combat Air Vehicle Configurations by inserting slots - Ali, U; Chadwick, E (The International Journal of Multiphysics, 2016)
The objectives of the present study on Unmanned Combat Air Vehicles (UCAVs) are two-fold: first to control the flow by inserting leading-edge and cross-flow slots and analysing the viscous flow development over the outer panels of a flying-wing configuration to maximise the performance of the elevons control surfaces; second to predict high-lift performance particularly the maximum-lift characteristics. This is demonstrated using a variety of inviscid Vortex Lattice Method (VLM) and Euler, and viscous CFD Reynolds Averaged Navier-Stokes (RANS) methods. The computational results are validated against experiment measured in a wind tunnel. Two flying-wing planforms are considered based around a generic 40˚ edge-aligned configuration. The VLM predicts a linear variation of lift and pitching moment with incidence angle, and substantially under-predicts the induced drag. Results obtained from RANS and Euler agree well with experiment.